FML-ELISA a novel diagnostic method for detection of feline leishmaniasis in two endemic areas of Iran - Foroughi-Parvar, Faeze (J Parasit Dis, 2020)
Although canids are regarded as major reservoir hosts for Leishmania infantum, feline leishmaniasis are reported sporadically from different endemic foci of Mediterranean visceral leishmaniasis (VL). Despite the risk of parasite transmission between human and other animals, most of the studies are limited to dogs and few studies are focused to investigate Leishmania sp. among other mammals. This project was aimed to detect L. infantum antibodies of cats in two VL endemic regions of Iran by Fucose Mannose Ligand (FML) and soluble L. infantum antigen (SLA) ELISA. Forty nine stray cats of different age and sex, from Fars and Ardabil provinces (two VL endemic loci of Iran) were sampled, then tested for L. infantum by FML and SLA-ELISA. Sixteen percent (8/49) of cat sera were reported positive by FML-ELISA. SLA-ELISA showed 18.3% (9/48) positive cases in cats. Sensitivity of FML-ELISA was calculated 57% and SLA ELISA 25%. Specificity of FML and SLA ELISA were assessed 78% and 68% respectively. Kappa coefficient of agreement between FML and SLA-ELISA was detected on 0.45. As feline leishmaniasis could be a potential risk in endemic areas, FML-ELISA could be considered as an appropriate examination to detect leishmaniasis in cats.